2023
DOI: 10.3390/plants12061326
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Nitrogen Rate and Improvement of Nitrogen Use Efficiency without Loss of Peanut Yield by Regional Mean Optimal Rate of Chemical Fertilizer Based on a Multi-Site Field Experiment in the North China Plain

Abstract: It is important to quantify nutrient requirements and optimize fertilization to improve peanut yield and fertilizer use efficiency. In this study, a multi-site field trial was conducted from 2020 to 2021 in the North China Plain to estimate nitrogen (N), phosphorus (P), and potassium (K) uptake and requirements of peanuts, and to evaluate the effects of fertilization recommendations from the regional mean optimal rate (RMOR) on dry matter, pod yield, nutrient uptake, and fertilizer use efficiency. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…These authors reported that increasing crop density by 30% in combination with a 15% lower base nitrogen fertilizer rate increased grain yield by more than 6%, while PFP N increased by about 25%. Similar results have been reported for rice, cotton, and peanut [46][47][48][49].…”
Section: Discussionsupporting
confidence: 89%
“…These authors reported that increasing crop density by 30% in combination with a 15% lower base nitrogen fertilizer rate increased grain yield by more than 6%, while PFP N increased by about 25%. Similar results have been reported for rice, cotton, and peanut [46][47][48][49].…”
Section: Discussionsupporting
confidence: 89%
“…In a methodological publication by Hu et al [26], a hypothesis was formulated that the optimal fertilizer doses can be determined via yield-fertilizer rate response modeling. For this purpose, the authors analyzed dozens of experiments with peanut plants located on the North China Plain.…”
Section: Balanced Fertilization As Key To Efficient N Usementioning
confidence: 99%